CODE-SWITCHING AS A PEDAGOGICAL RESOURCE IN BILINGUAL ONLINE CLASSROOMS - Emily Carter (International Journal of Literature and Language Studies, 2026)
This article investigates teacher and learner code-switching in bilingual online classrooms within the broader field of linguistics and applied language studies. The study uses twelve recorded online English lessons and 360 chat messages from intermediate bilingual learners and applies interactional discourse analysis supported by a functional coding scheme. The main finding is that code-switching was most frequent during clarification, classroom management, affective support, and vocabulary explanation. The article argues that strategic switching can support comprehension and participation when it is purposeful rather than automatic. The discussion is relevant to researchers, teachers, curriculum designers, and graduate students who need concise but systematic models of linguistic inquiry.